Effectiveness of two protocols of antibiotic therapy in the treatment of pneumonia in pregnant women - N. S. Nadirkhanova; M. M. Asatova; D. Zh. Aniyozova (Лечащий Врач)
Comparative analysis of effectiveness of two protocols of antibiotic therapy in the treatment of community-acquired pneumonia (CAP) in pregnant women was performed. The study included 98 pregnant women with severe CAP. The first group consisted of 45 pregnant women with CAP who underwent combined therapy with ceftriaxone and erythromycin. The second group consisted of pregnant women who were prescribed penicillin. The results showed that it is advisable to start antimicrobial therapy with monotherapy and, if necessary, add a second antibiotic. The conclusion about the effectiveness or inefficiency of antimicrobials should be done on average after 48–72 hours.